Innovative application of qualitative method in studying indigenous community’s mental health - Choudhry, Riaz Fahad (2019)
Background. The indigenous communities are the native communities, having a historical continuity with pre-invasion and pre-colonial societies that developed on their territories. The health research on indigenous people in developed countries has established guidelines for ethical conduct of research on these communities. However, there is a lack of such guidelines in Asian indigenous communities. Research Purpose. The modicum of research attention to indigenous marginalized communities from mental health perspectives has become the basis of highlighting some of the issues faced by researchers when doing a study on indigenous groups. Method. This paper argues that culturally appropriate indigenous methods must be adopted when working with marginalized communities, with the aim to decolonize research from western world view. The selection of appropriate methods in studying marginalized communities has been highlighted. The past literature suggests choosing culturally appropriate methods when working with marginalized indigenous communities. Population. A methodological recommendation,(encompassing qualitative, collective, participatory), and empowerment frameworks has been derived from in-depth study of indigenous Kalasha community in Pakistan using Interpretative Phenomenological Analysis (IPA). The aim of the project was to explore the resilience mechanisms (identification of cultural protective factors), and mental health conceptualization of Kalasha. Analysis. IPA was used for detailed analysis using a two-stage interpretation process also called double hermeneutic. The significance and implications of using IPA to study indigenous populations has been highlighted. Implications. This study shows appropriate methodological recommendations for health researchers in order to study marginalized indigenous communities.